RANITIDINE CAN POTENTIATE THE PROKINETIC EFFECT OF ITOPRIDE AT LOW DOSES- AN IN VITRO STUDY - Butt, Aroosa Ishtiaq; Khan, Bushra Tayyaba; Khan, Asma; Khan, Qamar-uz-zaman (Journal of Ayub Medical College Abbottabad, 2017)
Background: Gastroparesis and GERD occur concomitantly in 40 percent of the cases. Prokinetic drugs and acid blockers are employed as the main treatment modality. Ranitidine is an acid blocker with additional prokinetic activity and Itopride is a known prokinetic drug. This study was designed to observe the synergistic potentiating prokinetic effect of Ranitidine on itopride on isolated duodenum of rabbits. Methods: Ranitidine (10-5-10-3) and itopride (10-6-10-5) were added in increasing concentrations to isolated duodenum of rabbits and contractions were recorded on PowerLab Data acquisition unit AHK/214. Cumulative dose response curves were constructed. The potentiating prokinetic effect of Ranitidine on itopride was seen by using a fixed dose of ranitidine and cumulatively enhancing doses of itopride on iWorx. Results: Ranitidine and itopride produced a dose dependent reversible contraction of the isolated tissue of rabbits with ranitidine showing a max response of 0.124mV and itopride showing a maximum response of 0.131mV. Ranitidine was able to potentiate the prokinetic effect of itopride at low doses but at high dose the effect began to wane off. Conclusion: Ranitidine and itopride produce a statistically significant synergistic potentiating prokinetic effect at low doses in vitro. Keywords: Ranitidine; Itopride, Prokinetic, Outcome